Wine involvement interaction with dining group dynamics, group composition and consumption behavioural aspects in USA restaurants. Issue 1 (11th March 2019) - Bruwer, Johan; Cohen, Justin; Kelley, Kathleen
Abstract : Purpose: The importance of the wine involvement construct in explaining consumers' wine consumption behaviour is widely acknowledged in the literature, as is the social nature of dining out with others. Yet, there is a paucity of research examining the relationships between how this construct interacts with dining group dynamics and wine consumption behavioural aspects in the restaurant environment. This study aims to investigate these aspects in US restaurants. Design/methodology/approach: Utilising an online survey that yielded a sample of 513 respondents from across the USA who frequented all the recognised restaurant categories, respondents are segmented into low and high wine involvement categories using a reliable wine involvement scale. The authors examine differences between various dining group dynamics, dining group composition, main choice factors when ordering wine and method of ordering wine in US restaurants. Findings: The authors find that diners' level of involvement with wine provides sharp insights into several significant differences between involvement and dining group dynamics, group composition, choice factors when ordering wine and method of ordering wine in restaurants. High involvement diners dine out in larger groups, order more wine, spend more money on wine, are more often the main decision-maker ordering wine for the dining group and use wine menus and wall board displays more often when ordering than low involvement diners. They are also more discerning about the taste of wine, grape variety and wine style in terms of choice factors when ordering. Practical implications: The nature and dynamics of dining groups are aspects that have profound implications, in various ways, for the restaurant industry. The level of involvement diners have with wine is a strong predictor of various outcomes in terms of dining group behavioural aspects regarding wine. Wine-related restaurant category-specific profile descriptions, such as those developed in this study, can be helpful for restaurants when creating business strategies. Originality/value: The authors make a substantive contribution by being the first study to examine the relationships between dining group dynamics, dining group composition and behavioural aspects concerning wine consumption and involvement in the restaurant environment. The authors then map this information to derive wine-related profile descriptions for all US restaurant categories.